PENGEMBANGAN STRATEGI PEMBELAJARAN BIOLOGI UNTUK MENINGKATKAN KEBERMAKNAAN KONSEP DITINJAU DARI KEMAMPUAN INGATAN DAN KETELITIAN KERJA - ALVI ROSYIDI (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2004)
The aim of this research were to study the influence of using the scientific method on these following aspects: (1) The improvement of concept of 4 ,h semester’s subject of Biological Education, FKIP UNS, (2) Whether the memory capabilities can be used as a predictor or not, (3) The Carefulness can be used as a significant predictor and (4) contribution of each predictor on that improvement.Descriptive-quantitative research methods with expofacto were used, t test and regression were used to analyze the data. Data are collected by test method and it’s collection with two design; comparative and correlative on 30 samples of the 4 '* semester’s student.The result showed that the scientific method could raise the improvement of subject concept only slightly with no statistical differences. Beside, there is a positive correlation between either the memory capabilities or carefulness and the improvement the concep